Pengaruh Brand Image, Word of Mouth, dan Brand Community Terhadap Loyalitas Pelanggam Pengguna Smartphone Xiaomi (Studi Pada Komunitas Mi Fans Kota Malang) - Ahmad Tajul Minan; Muhammad Mansur; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTSThis research was conducted in the Mi Fans community in Malang City. This type of research is an explanatory research (quantitative research) through a quantitative approach. The purpose of this study was to determine the effect of brand image, word of mouth, and brand community on customer loyalty. The independent variables used are brand image, word of mouth, and brand community, while the dependent variable is customer loyalty. The sample used in this study was 80 respondents who are members of the Malang City Mi Fans community. Data collection techniques using a questionnaire. The analytical methods used are instrument test, multiple linear regression analysis, classic assumption test, determination test, f test and t test using the help of SPSS computer data processing software. The results of this study indicate that brand image has a positive effect on customer loyalty, word of mouth has a positive effect on customer loyalty, brand community has a positive effect on customer loyalty. Keywords: Brand Image, Word Of Mouth, Brand Community, Customer LoyaltyABSTRACTSThis research was conducted in the Mi Fans community in Malang City. This type of research is an explanatory research (quantitative research) through a quantitative approach. The purpose of this study was to determine the effect of brand image, word of mouth, and brand community on customer loyalty. The independent variables used are brand image, word of mouth, and brand community, while the dependent variable is customer loyalty. The sample used in this study was 80 respondents who are members of the Malang City Mi Fans community. Data collection techniques using a questionnaire. The analytical methods used are instrument test, multiple linear regression analysis, classic assumption test, determination test, f test and t test using the help of SPSS computer data processing software. The results of this study indicate that brand image has a positive effect on customer loyalty, word of mouth has a positive effect on customer loyalty, brand community has a positive effect on customer loyalty. Keywords: Brand Image, Word Of Mouth, Brand Community, Customer Loyalty